Does a positive family history influence the presentation of breast cancer? - Yip, Cheng Har; Mohd Taib, Nur Aishah; Lau, Peng Choong (West Asia Organization for Cancer Prevention, 2008)
Having a family history of breast cancer does not appear to have much impact on the health-seeking behavior of women. Even though there were more screen detected cancers, these comprised only 10% of the group with family history. Public education should target women at risk ie with family history to encourage these women to present earlier and to undergo screening for breast cancer.